More Than the Win: The Relation between Appetitive Competition Motivation, Socialization, and Gender Role Orientation in Women's Football - Meyer-Parlapanis, Danie; Siefert, Sabrina; Weierstall, Roland (Frontiers in Psychology, 2017)
The ability to produce peak performance plays a decisive role in the success of athletes in competitive contest situations. Levels of appetitive competition motivation (ACM), i.e. the desire to defeat an opponent independent of secondary reinforcing factors, were assessed in professional female football/soccer players in the premier and regional leagues, using club level as the measurement of sport success. Furthermore, the influence of social environments predominantly encouraging masculine and competitive play behavior and the players’ perceptions of their own gender role orientations were investigated. 90 female football players from the German premier league (44) and regional leagues (46) participated (age: M = 24, SD = 5 years). Questionnaires ascertaining ACM and self-perceptions of gender via gender-role stereotypes, childhood play behavior and style of upbringing were utilized. Premier league athletes showed a significantly greater inclination towards direct sporting confrontations. Almost 50% of the variance in ACM between the premier and regional league athletes was determined by modern upbringing style and the development of gender roles not corresponding to classic female gender stereotypes. The results emphasize the significance of ACM as an important facet in competitive sports and illustrate the influence of socialization on athletic performance.